2018
DOI: 10.1177/1533033818781405
|View full text |Cite
|
Sign up to set email alerts
|

High TSTA3 Expression as a Candidate Biomarker for Poor Prognosis of Patients With ESCC

Abstract: Esophageal squamous cell carcinoma is the sixth most lethal cancer worldwide and the fourth most lethal cancer in China. Tissue-specific transplantation antigen P35B codifies the enzyme GDP-d-mannose-4,6-dehydratase, which participates in the biosynthesis of GDP-l-fucose. GDP-l-fucose is an important substrate involved in the biosynthesis of many glycoproteins. Cancer cells are often accompanied by the changes in glycoprotein structure, which affects the adhesion, invasion, and metastasis of cells. It is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The difference was also significant in 60 paired cancer tissues and adjacent normal tissues ( P = 0.000) (Figure 1 F) . Correlation analysis between protein expression and clinicopathological factors showed that the high expression of TSTA3 was also significantly associated with late clinical stage, more lymph node metastasis and poor prognosis for ESCC patients 21 . Combining with TSTA3 as a fucose synthesis related enzyme, we speculated that abnormal fucosylation might participate in the progress of ESCC and TSTA3 might serve as a novel biomarker for prognosis of ESCC patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference was also significant in 60 paired cancer tissues and adjacent normal tissues ( P = 0.000) (Figure 1 F) . Correlation analysis between protein expression and clinicopathological factors showed that the high expression of TSTA3 was also significantly associated with late clinical stage, more lymph node metastasis and poor prognosis for ESCC patients 21 . Combining with TSTA3 as a fucose synthesis related enzyme, we speculated that abnormal fucosylation might participate in the progress of ESCC and TSTA3 might serve as a novel biomarker for prognosis of ESCC patients.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 508 ESCC patients with FFPE samples used for WGS were recruited from Shanxi and Xinjiang provinces in China. The description of the clinical characteristics of the 508 samples was presented in our previous study 21 . A total of 155 ESCC patients with fresh frozen tissues used for both WGS and transcriptomic sequencing were recruited from Shanxi provinces in China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been reported as an oncogene in hepatocellular carcinoma 35 , clear cell renal cell carcinoma 36 , triple-negative breast cancer 37 , and non-small-cell lung cancer 38 . TSTA3, also known as GFUS, participates in the pathway of transporting to the Golgi apparatus as well as metabolism 39 , and is considered an oncogene in many cancers including esophageal squamous cell carcinoma 40 . To the best of our knowledge, this is the first study to report the correlation of RALY and TSTA3 with overall survival in head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%